METHODOLOGY OF ASSESSMENT AND SELECTION OF ECONOMIC FACTORS CONDITIONING THE OPERATION OF INTEGRATED LOGISTICS CENTRES - Leszek MINDUR; Grzegorz SZYSZKA (Scientific Journal of Silesian University of Technology. Series Transport)
The article addresses the overall body of problems pertaining to economic factors conditioning the construction and operation of integrated logistics centres (ILCs). These problems are among the most fundamental decision-making dilemmas related to such investments. The authors of the article have discussed the methodology of assessment and selection of economic factors for the cost-effective construction and operation of ILCs by taking the perspective of entities involved in the construction and functioning of these centres into consideration. Model ILCs are understood as facilities of a specific spatial and functional nature, along with all the infrastructure and organization, where logistics services are rendered in the scope of receipt, storage, distribution and release of goods, supported by auxiliary services provided by businesses independent of forwarders or recipients[3]. From the perspective assumed in the article, logistics centres are considered as projects implemented by both privately owned and public entities, which are open to participation with different economic entities representing the ILC sector, as well as other industries performing their logistics operations on the centre’s premises and using its infrastructure. The article draws from the authors’ own experience, research and insights.